Equally delighted every time. Jarosław Iwaszakiewicz and paintings by Caravaggio - Peroń, Małgorzata (Studia Teologiczne Białystok Drohiczyn Łomża, 2024)
Caravaggio's painting is an important source of inspiration in Jarosław Iwaszkiewicz's work. In Travels to Italy, Iwaszkiewicz wrote a literary catalog of the works of the Italian Baroque master. His attention focuses on the interpretation of works from an existential perspective. In the book Travels to Italy, the images are subjected to careful observation. Iwaszkiewicz provides the location of the works, titles, and details of the painting, giving viewing these works a metaphor for discovering spiritual and metaphysical truths. In the literary works from Journey to Italy and Fame and Glory, painting becomes the stage of a theater in which the viewer turns into one of the participants of the presented events. The invitation accepted by Iwaszkiewicz to enter the interior of painting events emphasizes his concept of art. Art shows man's struggle with his own corporeality, imperfections and transience, and it reveals the desire to see a different, spiritual space.